2021
DOI: 10.5430/ijhe.v11n1p1
|View full text |Cite
|
Sign up to set email alerts
|

University Academics’ Perceptions Regarding the Use of Information Technology Tools for Effective Formative Assessment: Implications for Quality Assessment through Professional Development

Abstract: The study sought the perceptions of university academics on the use of IT tools for the formative assessment (FA) of students’ learning outcomes. This study adopted a quantitative research approach and descriptive survey research design using a sample of 180 university academics. Academics’ perception questionnaire was used for data collection. The instrument with two clusters was properly validated, and its internal consistency reliability indies found to be 0.79 and 0.85 for clusters A and B using the Cronba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Another methodology that has been pointed out as a contribution to the development of general competences is curricular internships, as mentioned by Paisey and Paisey (2010) in relation to Scotland and Covas et al (2017) in relation to Portugal. More recently, Ugwuanyi et al (2022) concluded that information technologies are indispensable for the implementation of formative assessment practices in higher education institutions in Nigeria. However, they found that gender and academic background influence teachers' perception of the use of these tools and their effective implementation.…”
Section: Development Of General Competences In Higher Educationmentioning
confidence: 99%
“…Another methodology that has been pointed out as a contribution to the development of general competences is curricular internships, as mentioned by Paisey and Paisey (2010) in relation to Scotland and Covas et al (2017) in relation to Portugal. More recently, Ugwuanyi et al (2022) concluded that information technologies are indispensable for the implementation of formative assessment practices in higher education institutions in Nigeria. However, they found that gender and academic background influence teachers' perception of the use of these tools and their effective implementation.…”
Section: Development Of General Competences In Higher Educationmentioning
confidence: 99%